2020
DOI: 10.1002/ar.24404
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix: The proteins that function throughout the body

Abstract: The idea and meetings that planned this issue focused on extracellular matrix (ECM) started over 4 years ago. The invitations were sent to investigators over 2 years ago and manuscripts have been submitted, reviewed, and edited since the summer and fall of 2018. Most of the manuscripts were published in early view in 2019, and we are thrilled to share the final collection. This volume contains 6 reviews, 13 original research papers, and 4 remembrances. Marion (Emmy) Gordon and I organized the articles into sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Secreted protein acidic and rich in cysteine (SPARC), also known as osteonectin or BM-40, is a prototype of the biologically active glycoprotein family that can bind to cells as well as to ECM components [ 6 ]. A prior study has reported a promoting role of SPARC in fibroblast migration, which facilitates granulation tissue formation, contributing to wound repair [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secreted protein acidic and rich in cysteine (SPARC), also known as osteonectin or BM-40, is a prototype of the biologically active glycoprotein family that can bind to cells as well as to ECM components [ 6 ]. A prior study has reported a promoting role of SPARC in fibroblast migration, which facilitates granulation tissue formation, contributing to wound repair [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue instead offers a broad overview, covering reviews and leading science exploring what the guest editors have grouped in seven major areas: (1) ECM overall structure, its genetics, and development; (2) advances in cancer; (3) vascular elements and ECM involvement in development; (4) inflammation and wound healing; (5) the role of collagen in special structures; (6) studies on ocular tissues, especially the cornea; and (7) extracellular vesicles. To accomplish this lofty task, the guest editors have gathered an array of international experts on the various, and varied, areas who collectively offer a comprehensive view of the many inhabitants of the ECM (Svoboda and Gordon, 2020, this volume).…”
mentioning
confidence: 99%